Self-monitoring blood pressure in hypertension – internet based survey of UK general practitioners - McManus, R; Hobbs, F; Hinton, L; Fletcher, B; Bray, E; Hayen, A; Mant, J; Potter, J (Royal College of General Practitioners, 2016)
Background Previous research suggests most UK General Practitioners (GPs) use self-monitoring of blood pressure (SMBP) to monitor control of hypertension rather than for diagnosis. This study sought to assess current practice in the use of self-monitoring and any changes in practice following more recent guideline recommendations. Aim To survey views and practice with regard to SMBP of UK GPs in 2015 and to compare to a previous survey in 2011. Design and setting Web-based survey of a regionally representative sample of 300 UK GPs. Method GPs completed an on-line questionnaire concerning the use of SMBP in the management of hypertension. Analyses comprised descriptive statistics, tests for between group differences (z test, Wilcoxon, chi square), and multivariate logistic regression. Results Results were available from 300 GPs (94% of those who started the survey). GPs reported using self-monitoring for diagnosing hypertension (169/291 (58% (95%CI 52-64))) and to monitor control (245/291 (84% (80-88))), the former significantly increased since 2011 (from 37% (33-41), p<0.001) with no change in monitoring for control. More than half of the GPs used higher systolic thresholds for diagnosis and treatment than recommended in guidelines and under half (120/169 GPs (42% (95%CI 36-47))) adjusted SMBP results for use in guiding treatment decisions. Conclusion Since new UK national guidance in 2011, GPs are more likely to use SMBP in the diagnosis of hypertension but significant proportions continue to use non-standard diagnostic and monitoring thresholds. The use of out of office methods to improve the accuracy of diagnosis is unlikely to be beneficial if sub optimal thresholds are used.